Detection of tetracycline and β-lactam resistance genes in Shigella species isolated from shigellosis cases in Iraq - Saeed, Mustafa M.; Jihad, Huda; O., Yasir J. (Iraqi Journal of Science, 2025)
Shigella is most commonly spread through the fecal-oral route, rather than through contaminated food, water, or swimming pools. A recent study collected 103 fecal samples of Shigella spp. from hospitals and laboratories across Iraq, spanning from July 2022 to June 2023. The samples were sourced from various cities, including Baghdad (65), Nasiriya (14), Babylon (11), Najaf (9), and Kirkuk (4). In this study, we examined Shigella species isolated from diarrhea samples for the presence of penicillin- and tetracycline-resistant genes. Tetracycline resistance genes (tetA and tetB) were detected in 96 (93%) and 84 (82%) isolates, respectively. Both genes (tetA and tetB) were detected in the same isolate 79 times (77%). While, β-lactam resistance genes (blaCTX-M and blaTEM) were detected in 87 isolates (84.5%) and 83 isolates (81%), respectively. However, 68 isolates (66%) exhibit both genes (blaCTX-M and blaTEM). Consequently, that detects the widespread use and overuse of penicillin and tetracycline. Thus, it is imperative to continue surveilling and regulating the spread of these genes to sustain the efficacy of existing antibiotics and develop new treatments for Shigella infections.